Dihydrogen driven cofactor recycling for use in bio-catalysed asymmetric organic synthesis - Lonsdale, T (2017)
Asymmetric reductions are used to produce chiral molecules, which are important precursors for the pharmaceutical industry. Bio catalytic reductions often display high enantioselectivity without the cost and toxicity associated with metal catalysis. However, unlike metal catalysts which use H2 directly, many useful redox-enzymes require the hydride donor NADH. NADH is expensive; therefore for a bio-catalytic process to be viable it must be recycled, usually by using a sacrificial carbon based substrate, generating super-stoichiometric amounts of waste. Two different methods for H2-driven NADH recycling are explored in this project: using soluble hydrogenases (SH) and, carbon particles modified with a hydrogenase and an NAD+-reductase moiety. The conductive carbon particles allow electrons from H2-oxidation to be channelled from the hydrogenase to the NAD+ reductase for reduction of NAD+. This project focuses on four main areas. The first looks at using the enzyme-modified particles for the production of high value chiral amines. A yield of >98% was achieved using the enzyme-modified particles with an L alanine dehydrogenase for H2 driven conversion of pyruvate to L-alanine. Moreover, a faster rate of reaction was demonstrated with the L-alanine dehydrogenase immobilised on particles versus with the L-alanine dehydrogenase in solution. The second section focuses on elevated temperature NADH recycling: an SH and an NAD+-reductase from a thermophilic organism were characterised. The NAD+-reductase was subsequently used as part of a system for recycling NADH at >35 °C. When demonstrated in combination with an enoate-reductase a 62 % yield was obtained for the reduction of 2 methyl 2 cyclopentenone. In the third strand SHs and enzyme-modified particles were investigated as recycling systems for NADH analogues. In summary, this thesis expands the scope for application of H2-driven biocatalytic reduction reactions.